Разработка единой методики расчетов по обеспечению безопасности газодымозащитников - Misyukevich Н. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
The technique is developed for calculations of safe work of rescuers in unsuitable environment for breath. It allows to carry out calculations without dependence from type and mark of an breathing apparatus, and also means of measurement of pressure. There is an opportunity to do calculations both in МПа, and in Bar. Such scales of manometers exist now. Besides calculation considers a stock for work of means of suppression and for breath rescueed.